2005
DOI: 10.1080/13638490400011165
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen in the management of spasticity due to cerebral palsy

Abstract: Intrathecal baclofen is a cornerstone in the treatment of spasticity in children. However, further research is required to set criteria for treatment. This paper offers insight into the national act on baclofen and the experience at the Nottingham University Hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
0
18
0
2
Order By: Relevance
“…26,28 After 83 test treatments, Vloeberghs et al reported five nonresponders and six children with a response not fulfilling the expectations of the caregivers. 28 It is unclear whether they tried only one ITB bolus per child or also higher doses in non-responders. We would encourage our colleagues to report more comprehensively on the design, results, and complications of ITB test treatments in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26,28 After 83 test treatments, Vloeberghs et al reported five nonresponders and six children with a response not fulfilling the expectations of the caregivers. 28 It is unclear whether they tried only one ITB bolus per child or also higher doses in non-responders. We would encourage our colleagues to report more comprehensively on the design, results, and complications of ITB test treatments in children.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, information on the children's weight and the incidence of side effects and complications was either limited or absent. 4,[26][27][28][29][30] Not all studies had a 100% success rate of test treatment. 26,28 After 83 test treatments, Vloeberghs et al reported five nonresponders and six children with a response not fulfilling the expectations of the caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,17,19,28 Deep vein thrombosis and pulmonary embolism have also been published as a case report. 12 In a retrospective report by Vloeberghs et al 29 that focused on the outcomes of ITB pump implantation in spasticity due to cerebral palsy, 10% of 85 patients undergoing a trial had spinal tap syndrome with no other complications reported. All of these were catheter trials.…”
Section: Discussionmentioning
confidence: 99%